Közösségi kommunikáció, szemlélet és attitűd: A helyi közösségek identitása a települések életében - Slezák-Bartos, Zsuzsanna (Kultúratudományi Szemle, 2024)
Community communication, view and attitude: The identity of local communities in the life of settlements The identity of local communities and their identification with the place of residence have a significant impact on the development and sustainability of settlements. Forming and maintaining an individual identity is a basic need of an individual's life, which is often associated with a feeling that the individual is a member of a community or belongs somewhere. This cultural identity is not only important for the individual, but also contributes to the cultural richness of the settlement and strengthens its community-forming power. Community spirit strengthens cohesion and solidarity in settlements, participants and members identify with their local community, willing to cooperate to achieve common goals and support each other in difficult times. The feeling of "belonging somewhere" helps individuals connect more closely to their residence, which can result a happier and more balanced life. Strong human relations improve the individual's quality of life and support the sustainable development of settlements. The identity of local communities creates a complex relationship between the community and the settlement, which is an essential factor in the quality of life, stability and sustainability of the settlements. Strengthening identity helps communities to strengthen themselves and develop in the future. An individual's emotional attachment to his place of residence affects its decisions, community participation and quality of life, so the understanding and supporting identity is essential in ensuring the development of urban communities. Research and measures in the fields of sociology, anthropology and urbanism help to create and strengthen a positive settlement identity; as well as they support the long-term planning of cities and strategic implementations.